Severely Disabled Readers. - Gunning, Thomas (1992)
Keywords: dept.rdg; faculty_collection; sabbatical_report

Assessing and correcting reading and writing difficulties - Gunning, Thomas G. (Allyn and Bacon, 1998)
Keywords: Ability testing; English language; Ability testing; Reading; Composition and exercises; Evaluation; Reading; Reading disability; Remedial teaching; English language; Study and teaching; dept.rdg; faculty_collection

Best books for beginning readers - Gunning, Thomas G. (Allyn and Bacon, 1998)
Keywords: Books and reading; Reading (Elementary); United States; United States; Children; dept.rdg; faculty_collection

Amazing Escapes: Illustrated with Photographs and Prints - Gunning, Thomas G. (Dodd, Mead, 1984)
Presents nine tales of escape and survival against great odds including escapes from a great white shark, a volcanic eruption, and a fall through a thunderstorm.
Keywords: Escapes; Juvenile literature; Juvenile literature; Adventure and adventurers; Juvenile literature; Survival; dept.rdg; faculty_collection

Unexplained Mysteries - Gunning, Thomas G. (Dodd, Mead, 1983)
Describes nine strange and, as yet, unexplained events including the man who lived after spending two days inside a whale's stomach, the sighting of a dinosaur-like creature in Africa, the moving coffins of Barbados.
Keywords: Curiosities and wonders; Juvenile literature; dept.rdg; faculty_collection

Visual Discrimination of Words and Reading Readiness - Shea, CA (Reading Teacher, 1968)
tex.unique-id: ISI:A1968ZD14700011
Keywords: dept.rdg; ⛔ No DOI found

Using the Newspaper with Disruptive Students - Criscuolo, Nicholas P.; Gallagher, Sally A. (Journal of Reading, 1989)
Citation Key Alias: ISI:A1989R846300009 tex.unique-id: [object Object]
Keywords: dept.rdg; ⛔ No DOI found

An attitude survey for sustained silent reading programs - Sadoski, MC (Journal of Reading, 1980)
tex.unique-id: ISI:A1980JS59700015
Keywords: dept.rdg; ⛔ No DOI found

Word Building - a Strategic Approach to the Teaching of Phonics - Gunning, TG (Reading Teacher, 1995)
tex.unique-id: ISI:A1995QK74000004
Keywords: dept.rdg; ⛔ No DOI found

Children’s Acquisition and Retention of Word Spellings - Dreyer, Lois G.; Luke, Stephen D.; Melican, Eileen K. (The Varieties of Orthographic Knowledge: II: Relationships to Phonology, Reading, and Writing, 1995)
Spelling is one of several important operations involved in the act of writing but until recently has received attention primarily in the applied domain. Orthographic abilities, because of their strong association with reading (e.g. Perfetti, 1985), are now of increasing interest to those who study the cognitive bases of literacy development. It is generally acknowledged that phonological processes underlie essential aspects of word recognition (Adams, 1990; Dreyer, 1989; Liberman, Shankweiler & Liberman, 1989; Stanovich, 1986; Wagner & Torgesen, 1987; Williams, 1986). An expanding body of research suggests that orthographic factors can account for a significant amount of variance in word recognition over and above phonological abilities (Cunningham & Stanovich, 1990; 1993; Dreyer, 1994; Stanovich & West, 1989; Stanovich, West & Cunningham, 1991).
Citation Key Alias: lens.org/083-701-708-807-487, pop00143
Keywords: Orthographic Knowledge; Phonological Awareness; Receptive Vocabulary; Target Word; Word Reading; dept.rdg

Cognitive profiles of reading-disabled children: comparison of language skills in phonology, morphology, and syntax: - Shankweiler, Donald; Crain, Stephen; Katz, Leonard; Fowler, Anne E; Liberman, Alvin M; Brady, Susan; Thornton, Rosalind; Lundquist, Eric; Dreyer, Lois G; Fletcher, Jack M; Stuebing, Karla K; Shaywitz, Sally E; et al. (Psychological Science, 1995)
A comprehensive cognitive appraisal of elementary school children with learning disabilities showed that within the language sphere, deficits associated with reading disability are selective: Phonological deficits consistently accompany reading problems whether they occur in relatively pure form or in the presence of coexisting attention deficit or arithmetic disability. Although reading-disabled children were also deficient in production of morphologically related forms, this difficulty stemmed in large part from the same weakness in the phonological component that underlies reading disability. In contrast, tests of syntactic knowledge did not distinguish reading-disabled children from those with other cognitive disabilities, nor from normal children after covarying for intelligence.
266 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-040-195-741-957 tex.type: [object Object]
Keywords: dept.rdg

Postcards from america - mullin,p - Gunning, TG (Journal of Reading, 1993)
tex.unique-id: ISI:A1993KU11700036
Keywords: dept.rdg; ⛔ No DOI found

The Need to Know Library - Gunning, TG (Journal of Reading, 1993)
tex.unique-id: ISI:A1993KU11700037
Keywords: dept.rdg; ⛔ No DOI found

The learning-disabled child - farnhamdiggory,s - Gunning, TG (Journal of Reading, 1993)
tex.unique-id: ISI:A1993KH66900025
Keywords: dept.rdg; ⛔ No DOI found

Why Does Baby Cry - Feagin,m, Feagin,c - Gunning, TG (Journal of Reading, 1991)
tex.unique-id: ISI:A1991ET96500028
Keywords: dept.rdg; ⛔ No DOI found

More Incredible True Adventures - Wulffson,dl - Gunning, TG (Journal of Reading, 1990)
tex.unique-id: ISI:A1990CZ75400034
Keywords: dept.rdg; ⛔ No DOI found

Readability of literature and popular titles - Gunning, TG (Journal of Reading, 1989)
tex.unique-id: ISI:A1989AQ58500029
Keywords: dept.rdg; ⛔ No DOI found

Selected from one more time - burnett,c - Gunning, TG (Journal of Reading, 1989)
tex.unique-id: ISI:A1989AQ58500028
Keywords: dept.rdg; ⛔ No DOI found

The ghosts of blackpoint - mullin,p - Gunning, TG (Journal of Reading, 1989)
tex.unique-id: ISI:A1989AQ58500027
Keywords: dept.rdg; ⛔ No DOI found

Big rigs - nentl,ja - Gunning, TG (Journal of Reading, 1987)
tex.unique-id: ISI:A1987G985500018
Keywords: dept.rdg; ⛔ No DOI found

Corvette, america supercar - hoffman,j - Gunning, TG (Journal of Reading, 1987)
tex.unique-id: ISI:A1987G985500017
Keywords: dept.rdg; ⛔ No DOI found

Kon-Tiki - Heyerdahl,t - Gunning, TG (Journal of Reading, 1987)
tex.unique-id: ISI:A1987G985500020
Keywords: dept.rdg; ⛔ No DOI found

The rattlesnake - green,cr, sanford,wr - Gunning, TG (Journal of Reading, 1987)
tex.unique-id: ISI:A1987G985500019
Keywords: dept.rdg; ⛔ No DOI found

Panic 5 - Hallman,r - Gunning, TG (Journal of Reading, 1987)
tex.unique-id: ISI:A1987G332400017
Keywords: dept.rdg; ⛔ No DOI found

High-Low Handbook - Libretto,ev - Gunning, TG (Journal of Reading, 1986)
tex.unique-id: ISI:A1986E825100021
Keywords: dept.rdg; ⛔ No DOI found

Incredible True Adventures - Wulffson,dl - Gunning, TG (Journal of Reading, 1986)
tex.unique-id: ISI:A1986E825100020
Keywords: dept.rdg; ⛔ No DOI found

Wrong level test - wrong information - Gunning, TG (Reading Teacher, 1982)
tex.unique-id: ISI:A1982NM65600004
Keywords: dept.rdg; ⛔ No DOI found